Numerical Study of the Effect of the Port Angle of the Superior Vena Cava Supplying Cannula on Hemodynamics in the Right Atrium in VV-ECMO - Xinrui Ma; Kaihang Xu; Bin Gao (Biomedicines)
Objective: To elucidate the pattern of the influence of the port angle of the superior vena cava supplying cannula (SVCS) on hemodynamics within the right atrium in VV-ECMO. Methods: A three-dimensional model of the right atrium was established based on CT images of a real patient. The 3D models of the SVCS and inferior vena cava draining cannula (IVCD) were established based on the Edwards 18Fr and Medos 22Fr real intubation models, respectively. Based on these models, three-dimensional models of the SVCS ports with bending angles of −90°, −60°, −30°, 0°, 30°, 60°, and 90° in the plane formed by the centerline of the SVCS and the center point of the tricuspid valve (TV) were established. Transient-state computational fluid dynamics (CFD) was performed to clarify the right atrium blood flow pattern and hemodynamic states at different SVCS port orientation angles. The velocity clouds, wall pressure, wall shear stress (WSS), relative residence time (RRT), and recirculation fraction (RF) were calculated to assess hemodynamic changes in the right atrium at different angles of the port of the SVCS. Results: As the angle of the port of the superior chamber cannula changed, the location of the high-velocity blood impingement from the SVCS changed, and the pattern of blood flow within the right atrium was dramatically altered. The results for the maximum right atrial wall pressure were 13,472 pa, 13,424 pa, 10,915 pa, 7680.2 pa, 5890.3 pa, 5597.6 pa, and 7883.5 pa (−90° vs. −60° vs. −30° vs. 0° vs. 30° vs. 60° vs. 90°), and the results for the mean right atrial wall pressure were 6788.9 pa, 8615.1 pa, 8684.9 pa, 6717.2 pa, 5429.2 pa, 5455.6 pa, and 7117.8 pa ( −90° vs. −60° vs. −30° vs. 0° vs. 30° vs. 60° vs. 90°). The results of the maximum right atrial wall WSS in the seven cases were 63.572 pa, 55.839 pa, 31.705 pa, 39.531 pa, 40.11 pa, 28.474 pa, and 35.424 (−90° vs. −60° vs. −30° vs. 0° vs. 30° vs. 60° vs. 90°), respectively, and the results of the mean right atrial wall WSS results were 3.8589 pa, 3.6706 pa, 3.3013 pa, 3.2487 pa, 2.3995 pa, 1.3304 pa, and 2.0747 pa (−90° vs. −60° vs. −30° vs. 0° vs. 30° vs. 60° vs. 90°), respectively. The results for the area percentage of high RRT in the seven cases were 3.44%, 2.23%, 4.24%, 1.83%, 3.69%, 7.73%, and 3.68% (−90° vs. −60° vs. −30° vs. 0° vs. 30° vs. 60° vs. 90°), and the results for the RF were 21.57%, 23.24%, 19.78%, 12.57%, 10.24%, 5.07%, and 8.05% (−90° vs. −60° vs. −30° vs. 0° vs. 30° vs. 60° vs. 90°). Conclusions: The more the port of the SVCS is oriented toward the TV, the more favorable it is for reducing RF and the impingement of blood flow in the right atrial wall, but there may be an increased risk of RRT. The opposite orientation of the SVCS port to the TV is not conducive to reducing flow impingement on the right atrial wall and RF.